Simulation Innovation to Redesign the Baccalaureate Curriculum to Address Population Health. Issue 5 (September 2018) - Mauro, Ann Marie P.; Tracey, Debora L.; LoGrippo, Maria Torchia; Anderson, Sharon; Bravo, Angelica; Byrne, Claire; Geissler, Bonnie; Escallier, Lori A.
Abstract : Prelicensure nursing curricula need to be redesigned to integrate and achieve key population health competencies. Nursing students in generic and second-degree programs had improved learning outcomes and significant increases in population health competencies across the curriculum using simulation-based learning activities developed through an academic-practice partnership. Simulation is an effective, interactive strategy that enhances student knowledge, skills, and competencies in addressing population health. Abstract : Supplemental digital content is available in the text.